Dammed if you do, dammed if you don't: The impact of economic rationalist imperatives on the adaptive capacity of public infrastructure in Brisbane, Australia and Cork, Ireland. (8th June 2020) - Tangney, Peter
Abstract: This paper presents a comparative analysis of catchment management dams in Cork, Ireland and Brisbane, Australia to demonstrate how interactions between municipal government and expert advisors for public infrastructure administration can constrain community climate adaptation. The analysis highlights how neoliberal economic rationalism can appropriate public value choice under the guise of technocratic expertise. Experts are often considered responsible agents for the effective administration of public infrastructure, even when ostensibly technical decisions concerning infrastructure management seem to demand normative, political input. Technocratic administration arising from economic rationalist priorities can thereby exacerbate the hazards presented by climate variability and advancing climate change. Climate risk managers in both cases over‐relied on operating protocols and the expertise of engineers to administer public infrastructure in pursuit of economic priorities. When operating protocols proved insufficient in the face of climate extremes, however, blame was assigned to experts despite their making all available attempts to avert disaster. Through analysis of these cases, the paper discusses the need for normative transparency in expert‐led public administration and better integration of multi‐level governance for climate resilience when pursuing economic rationalist imperatives.